2019
DOI: 10.12688/f1000research.20575.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding the phenotypes of osteoarthritis

Abstract: Recent research in the field of osteoarthritis (OA) has focused on understanding the underlying molecular and clinical phenotypes of the disease. This narrative review article focuses on recent advances in our understanding of the phenotypes of OA and proposes that the disease represents a diversity of clinical phenotypes that are underpinned by a number of molecular mechanisms, which may be shared by several phenotypes and targeted more specifically for therapeutic purposes. The clinical phenotypes of OA supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
114
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 54 publications
0
114
0
1
Order By: Relevance
“…Arthritis is the pathology of the full joint, which leads to degeneration of cartilage, meniscus, tendon and bone due to a highly inflammatory environment over a long time [ 4 ]. COX-1/2 pathway regulates the most common inflammatory cytokines involved in the degradation of joints, which are known for joint destruction but also because of underlying pain associated with arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arthritis is the pathology of the full joint, which leads to degeneration of cartilage, meniscus, tendon and bone due to a highly inflammatory environment over a long time [ 4 ]. COX-1/2 pathway regulates the most common inflammatory cytokines involved in the degradation of joints, which are known for joint destruction but also because of underlying pain associated with arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple kinds of arthritis, with osteoarthritis and rheumatoid arthritis being the two primary forms [ 1–3 ]. It is the disease of the whole joint, which involves activation of catabolic enzymes, nitric oxide synthase-2, cyclooxygenases-(COX)-2, degradation of the matrix through matrix metalloproteinases (MMP-1, MMP-3 and MMP-13), a disintegrin and metalloproteinase with thrombospondin-1 domains 4 and 5 and activation of cytokines, such as (IL-6, IL-1β and TNF-α), leading to the destruction of the total joint and chronic pain [ 4–7 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…OA has been historically categorized as non-inflammatory arthritis [2,4]. However, synovitis plays a key role in cartilage damage and vice versa [1,2,5]. Occurring in either early or late stages of OA, synovitis leads to increase in catabolic and proinflammatory mediators such as cytokines, nitric oxide, prostaglandin E, and neuropeptides.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-in ammatory treatment options (anti-TNF-alpha and anti-IL-1R1) [3][4][5] have been tested interventional trial including patient populations with de ned OA, however with no or limited description to their phenotype that may indicate differential response across different sub-populations. It has been suggested that a drug like lutikizumab (monoclonal antibody against IL1α/β) would work in patients with an in ammatory phenotype, while sprifermin (recombinant and truncated form of broblast growth factor 18) would work in patients with cartilage repair endotype [6][7][8]. There is a clear medical need to identify phenotypes in OA to enable development of more e cacious drugs.…”
Section: Introductionmentioning
confidence: 99%